Developing a Community-Engaged Research-Creation Methodology through the Resonance Project - Waterman, Ellen; Franklin, Gale (MUSICultures, 2025)
In this article, we outline an emergent community-engaged research-creation (CE-RC) methodology that builds on principles from performative ethnography, community engagement, and care-full improvisation. CE-RC was developed through the Resonance Project (2020-23), in which we tested, reflected on, and refined our ideas in collaboration with musicians from marginalized communities. Drawing on both ethnographic data and analysis of collaborative artistic creations, we argue that CE-RC has high potential as a participatory applied methodology through which researchers and community collaborators together can advocate for positive social change.